JURIDICAL ANALYSIS OF LEUSER ECOSYSTEM AREA IN NANGGROE ACEH DARUSSALAM - Edy, Triono (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Abundant Natural Resources is a priceless gift. In some region, maximum utilization of the natural resources is a must, but often without considering many other aspects including the environmental impact. The indication of natural resources exploitation can be seen from the creation of many regulations by the Indonesian Supreme Court. One of the regulation is the Regulation of Nanggroe Aceh Darussalam (NAD) Governor No. 5 Year 2014 about KEL. This research describes on how to manage the Leuser Ecosystem Area (KEL) viewed from regional autonomy aspect especially in NAD. This research is also based on writersâ dissertation that was done in 2005. This research uses normative law methods, uses primer, secondary and tertiary data sources by doing literature and descriptive- qualitative review. This paper describes the environmental law which is connected with other fields. The result shows that the NAD government need to review and to reconsider their policy and regulation related to KEL in accordance to the Ministry of Home Affairs Regulation No. 53 Year 2011 about the Establishment of Regional Legal Products. It is expected that the natural resources exploitation will no longer be oriented only towards economical profit. The natural resources should be used to develop prosperous society.